Students’ Level of Awareness in the Practice of Jinayah Knowledge at Universitas Islam Negeri Alauddin, Makassar: Perspectives from Islamic Law and Islamic Education - Shabir Umar, Muhammad; Damopolii, Muljono; Yusuf T., M.; Idham, Idham; Fathurrahman, Fathurrahman (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
Law that regulates human activities in daily life is one of the essential aspects to be studied, including Islamic law. This is particularly relevant for students of the Islamic Religious Education Program at the Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar, who study fiqh (Islamic jurisprudence), especially jinayah (crime), and are therefore considered to have sufficient understanding and are expected to practice this knowledge in the form of observable behavior. This study employed a mixed-methods approach, combining quantitative and qualitative methods within a single study to obtain a more comprehensive and in-depth understanding of the research phenomenon. The quantitative data were collected from questionnaires, while the qualitative data were derived from interview results and relevant literature related to the research focus. The findings indicate that students’ practice of their knowledge falls within the moderate category, with a percentage of 66.67%. The effectiveness of law enforcement depends on legal norms, legal structures, and legal awareness. In this context, however, legal awareness becomes the primary aspect, as with legal awareness students are able to behave properly without engaging in actions that contradict or violate the law. Therefore, within the context of Islamic law, public awareness, more specifically students’ awareness, serves as the key factor determining whether the law operates effectively or not. In addition, in the context of Islamic education, an individual’s knowledge plays a significant role in shaping legal awareness.